1996
DOI: 10.1210/endo.137.4.8625900
|View full text |Cite
|
Sign up to set email alerts
|

Pituitary adenylate cyclase-activating polypeptide regulates prolactin promoter activity via a protein kinase A-mediated pathway that is independent of the transcriptional pathway employed by thyrotropin-releasing hormone.

Abstract: The hypothalamic peptide, pituitary adenylate cyclase-activating polypeptide (PACAP), can efficiently increase cAMP levels in pituitary cells and release a number of pituitary hormones, suggesting an important physiological role for this peptide in pituitary function. Exposure of GH3 rat pituitary cells to PACAP results in increases in cellular cAMP levels, PRL promoter activity, and PRL messenger RNA levels. We have employed this system to further characterize PACAP regulation of PRL gene expression. RT-PCR a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…Cytofluorimetric studies, conducted on dispersed rat pituitary cells, have shown that PACAP, acting through three different mechanisms, induces calcium elevation in all categories of endocrine cells Gracia-Navarro et al, 1992;Rawlings et al, 1993Rawlings et al, , 1994Rawlings and Hezareh, 1996;Alarcón and García-Sancho, 2000). Consistent with this observation, PACAP stimulates the release of GH, adrenocorticotropin, LH, follicle-stimulating hormone (FSH), PRL (Goth et al, 1992;Hart et al, 1992;Coleman and Bancroft, 1993;Koch and Lutz-Bucher, 1993;Perrin et al, 1993;Arbogast and Voogt, 1994;Hashizume et al, 1994;Velkeniers et al, 1994;Coleman et al, 1996;Martínez-Fuentes et al, 1998c;Ortmann et al, 1999) and somatolactin (Azuma et al, 2009). The effects of PACAP on the different pituitary cell types are summarized in Table 9.…”
Section: B Effects Of Pituitary Adenylate Cyclase-activating Polypepmentioning
confidence: 69%
“…Cytofluorimetric studies, conducted on dispersed rat pituitary cells, have shown that PACAP, acting through three different mechanisms, induces calcium elevation in all categories of endocrine cells Gracia-Navarro et al, 1992;Rawlings et al, 1993Rawlings et al, , 1994Rawlings and Hezareh, 1996;Alarcón and García-Sancho, 2000). Consistent with this observation, PACAP stimulates the release of GH, adrenocorticotropin, LH, follicle-stimulating hormone (FSH), PRL (Goth et al, 1992;Hart et al, 1992;Coleman and Bancroft, 1993;Koch and Lutz-Bucher, 1993;Perrin et al, 1993;Arbogast and Voogt, 1994;Hashizume et al, 1994;Velkeniers et al, 1994;Coleman et al, 1996;Martínez-Fuentes et al, 1998c;Ortmann et al, 1999) and somatolactin (Azuma et al, 2009). The effects of PACAP on the different pituitary cell types are summarized in Table 9.…”
Section: B Effects Of Pituitary Adenylate Cyclase-activating Polypepmentioning
confidence: 69%
“…VIP is a recognized stimulator of PRL release, whereas the role of PACAP38 on PRL synthesis and release may be species dependent [49]. However, additivity of PACAP38 and TRH effects on the PRL promoter has already been described in the pituitary cell line GH3 [50]. In our study, concentrations of VIP and PACAP38 (1–2 n M ) able to elicit half-maximal activation of ERK in GH4C1 cells are compatible with a physiological role of this transduction pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Although cAMP generated upon stimulation with VIP can activate the secretion of PRL (Guild and Drummond, 1983;Onali et al, 1983), no such relationship was found for TRH. The main action of TRH on PRL secretion was instead attributed to elevations in [Ca 2+ ] cyt , and the activation of PKC (Gershengorn, 1986 (Coleman et al, 1996;Hayakawa et al, 2002;Lin et al, 1996). Likewise, TRH does impact gene expression, because it directly stimulates the promoter of the gene encoding PRL via activation of MAPK (Wang and Maurer, 1999).…”
Section: +mentioning
confidence: 99%